The Obstetric Connection: Midwives and Weasels within and beyond Minoan Crete - Simone Zimmermann Kuoni (Religions, 2021)
The Minoan peak sanctuaries call for systematic comparative research as an island-bound phenomenon whose significance to the (pre)history of medicine far transcends the Cretan context: they yield clay anatomical offerings attesting to the earliest known healing cult in the Aegean. The peak sanctuary of Petsophas produced figurines of weasels, which are usually interpreted as pests, ignoring their association with votives that express concerns about childbirth, traditionally the first single cause of death for women. The paper draws from primary sources to examine the weasel’s puzzling bond with birth and midwives, concluding that it stems from the animal’s pharmacological role in ancient obstetrics. This novel interpretation then steers the analysis of archaeological evidence for rituals involving mustelids beyond and within Bronze Age Crete, revealing the existence of a midwifery koine across the Near East and the Mediterranean; a net of interconnections relevant to female therapeutics which brings to light a package of animals and plants bespeaking of a Minoan healing tradition likely linked to the cult of the midwife goddess Eileithyia. Challenging mainstream accounts of the beginnings of Western medicine as a male accomplishment, this overlooked midwifery tradition characterises Minoan Crete as a unique crucible of healing knowledge, ideas, and practices.